Microplastics ingestions by wild and aquaculture marine bivalves: A systematic review on field investigation study - Ni Luh Gede Rai Ayu Saraswati (Sustinere: Journal of Environment and Sustainability, 2023)
Plastics degradation has resulted in a major threat to marine organisms, including bivalves. Thirty-three peer-reviewed papers have been reviewed to understand the geographical spread of microplastics ingestion by marine bivalves, characteristics of microplastics ingested, and limitation of microplastics analysis globallly. Only studies on microplastics investigation in marine bivalves from wild and aquaculture area were selected. Marine bivalves are reported to accumulate microplastics from all marine environment compartments. High proximity area with intensive human activities is suggested to increase the uptake of microplastics by the bivalves. Microfibers and fragments are the common types of microplastics ingested by the bivalves around the world, with various sizes (0.45µm – <45mm) and number of particles per individual (20 – ~175 particles/individual). However, there is uncertainty when comparing the findings from one study to another due to the absence of international standard protocol and microplastics data base. Therefore, this limitation should be addressed prior to monitoring microplastics accumulation in marine bivalves.